Efektivitas Undang-Undang Nomor 39 Tahun 2007 Tentang Cukai dalam Penegakan Hukum Terhadap Tindak Pidana Ekonomi Rokok Ilegal di Indonesia - Vincent Candela; Rasji Rasji (UNES Law Review, 2023)
This research aims to analyze legal regulations related to the distribution of excise-free cigarettes in Indonesia and law enforcement efforts. The research method used is normative juridical legal research with a conceptual and problem approach. The research results show that the distribution of illegal cigarettes has become a significant problem in Indonesia, with a large number of the population purchasing cigarettes outside the registered system. Even though Law Number 39 of 2007 concerning Excise has relevant provisions, there are still problems in enforcing the law against illegal cigarettes. Law enforcement is carried out both preventively and repressively, but there are still obstacles such as lack of awareness of producers and the public, weak regulations, as well as obstacles in supervision and enforcement. However, there are criminal and administrative sanctions that have been regulated to deal with the distribution of illegal cigarettes. In conclusion, the existing legal regulations are relatively effective but further efforts are still needed in enforcing the law against the distribution of illegal cigarettes in Indonesia.